Interrogating the specific challenges of teaching play texts in heterogeneous classrooms in the Eastern Cape - Hayes, Nicola (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2016)
This study is an autoethnographic reflection, rooted in Action Research based on my teaching experience in a multicultural high school environment in the Eastern Cape, South Africa. It is an analysis, in particular, of teaching play texts in two classes, Dramatic Arts and English Home Language, at matric level. A combination of discourse analysis and autoethnography formed the theoretical basis for the interpretation of data drawn from lesson transcripts, group interviews, learners' reflections and my own journalled reflections. This analysis has formed the foundation for a deeper reflection on culture, the colonist within, and the colonialism embedded with in my teaching, and in the education system more broadly. At a practical level, I suggest embracing student-led and co-led discussions of literature, as advocated by Mayer (2012), as well as transcultural readings (Keating, 2007), and Drama activities, as ideals in the teaching of play texts. These techniques are designed to encourage learners to develop intellectual authority as well as allowing them the space to enter discussions around culturally sensitive topics, while minimising the teacher's hierarchical, dominant position. I also argue for the importance of making culture an overt topic of conversation. White English-speaking South African culture, in particular has been prone to "invisibility" and, through this, an unspoken normative position, particularly in multicultural school environments. I challenge myself and others to engage in ongoing efforts to articulate our particular perception of our cultures, dynamic and diverse though they may be.
Keywords: Uncatalogued